A Systematic Review of Bone Anti-Resorptive Treatment Toxicity in Innate and Adaptive Immunity Cells: Osteonecrosis of the Jaws and Future Implications - Kyrgidis, Athanassios; Yavropoulou, Maria; Tilaveridis, Ioannis; Andreadis, Charalambos; Antoniades, Konstantinos; Kouvelas, Dimitrios (The Journal of Dentists, 2015)
Introduction: Bone anti-resorptive agents, namely bisphosphonates and denosumab are widely prescribed for the prevention of osteoporosis fractures and of cancer-related skeletal events. Osteonecrosis of the jaws (ONJ) has been reported for both drug categories. These agents have anti-proliferative effects in osteoclasts. We argue that because osteoclasts share their progenitor cells with macrophages, ONJ could be the result of reduced numbers and function of macrophages. Methods: We systematically searched MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials (CENTRAL) from inception through September 2014, for studies reporting the effects of bone-antiresorptive agents in the innate and adapted immunity. No limitations pertaining to study type were set. Results: Periosteal and endosteal tissues contain a discrete population of resident tissue macrophages. BPs cause apoptosis of macrophages in a dose and agent dependent manner. Increased cytotoxic activity by the γδ T cell population, could induce macrophage cell death causing local immune deficiency. Upon apoptotic stimuli, zoledronatepre-treated macrophages exhibit a significantly greater apoptotic rate. Long term BP exposed monocytes and macrophages may lead to functional impairment and reduced numbers of monocytic cells. Conclusions: Bone-anti-resorptive agents have the capacity of both functionally impairing and reducing the macrophage population. The currently available limited evidence suggests a plausible role of these agents in the pathogenesis of ONJ. Future studies both clinical and experimental should focus on the effects of these drugs in immune homeostasis.